Islamic public–private partnership model for Djibouti geothermal project financing: conceptual framework based on maqasid al-shariah - Ismail Mohamed, Kadra; Kassim, Salina (Academia Industry Networks (ACINET), 2023)
In view of its strategic location at the intersection of the Red Sea and Indian Ocean, Djibouti has capitalized on its geostrategic position by specializing in transport and logistical operations. Due to that, Djibouti is experiencing steady economic growth, however, a long-standing issue facing the economy is the energy deficit and high dependence on imported fossil fuels. Despite Djibouti being rich in renewable energy, it does not have natural oil, gas, coal, and hydropower, for that reason, Djibouti mostly depends on energy imports from Ethiopia and fossil fuel from the international market. Accordingly, the cost of the electricity is very high which has impeded the socioeconomic development of Djibouti. Thus, the Djibouti government has taken decisive action in exploring geothermal energy. The international experts have explored huge geothermal resources potential to meet the needs of consumption and commercially exportable geothermal reserve, nonetheless, the project is yet to be completed because of financial and technical constraints. Hence, there is a quest for a sustainable financing model that is cost effective, enhancing the fund accessibility, and helping successful completion of the project. The aim of this study is to propose for the development of Islamic Public-Private Partnership (PPP) financing based on Musharakah and Istisna. The combination between PPP and Islamic models is expected to accelerate sustainable investment for renewable energy, given the fact that Islamic PPP financing is based on Islamic principles, enabling the government to shift away from interest-based financing and accumulated interest that just keeps growing and increasing the national debt burden which is among the highest in Africa. The research adopts Maqasid Al-Shariah theory to develop a conceptual framework for Islamic PPP financing based on Musharakah and Istisna in the context of the Djibouti geothermal project.